Sox Gene Family Revealed Genetic Variations in Autotetraploid Carassius auratus - Huang, Xu; Wu, Chang; Gong, Kaijun; Chen, Qian; Gu, Qianhong; Qin, Huan; Zhao, Chun; Yu, Tingting; Yang, Li; Fu, Wen; Wang, Yude; Qin, Qinbo; et al. (Frontiers in Genetics, 2020)
The Sox gene family encoded transcription factors that played key roles in developmental processes in vertebrates. To further understand the evolutionary fate of the Sox gene family in teleosts, the Sox genes were comprehensively characterized in fish of different ploidy levels, including blunt snout bream (2n=48, Megalobrama amblycephala, BSB), goldfish (2n=100, Carassius auratus red var., 2nRCC), and autotetraploid Carassius auratus (4n=200, 4nRCC). The 4nRCC, which derived from the whole genome duplication (WGD) of 2nRCC, were obtained through the distant hybridization of 2nRCC (♀) × BSB (♂). Compared with the 26 Sox genes in zebrafish (2n=50, Danio rerio), 26, 47 and 92 putative Sox genes were identified in the BSB, 2nRCC and 4nRCC genomes, respectively, and classified into seven subfamilies (B1, B2, C, D, E, F, and K). Comparative analyses showed that 89.36% (42/47) of Sox genes were duplicated in 2nRCC compared with those in BSB, while 97.83% (90/92) of Sox genes were duplicated in 4nRCC compared with those in 2nRCC, meaning the Sox gene family had undergone an expansion in BSB, 2nRCC and 4nRCC, respectively, following polyploidization events. In addition, potential gene loss, genetic variations, and paternal parent SNP locus insertion occurred during the polyploidization events. Our data provided new insights into the evolution of the Sox gene family in polyploid vertebrates after several rounds of WGD events.